Analysis of Physico-Chemical Properties and Bacteriological Loads of Waste Water Effluent from Oxidation Pond at Woldia University, North Wollo, Ethiopia (International Journal of Sustainable Energy and Environmental Research, 2019)
Rivers are vital component of the biosphere that contains less than one percent of the world’s fresh water which is being polluted by indiscriminate disposal of domestic and industrial waste sewerage. The purpose of this study was to analysis the level of heavy metals and physico-chemical characteristics of wastewater effluent from oxidation pond. Samples were collected per month starting from May 2018 up to July2018. Three sampling ponds were selected purposefully among constructed 13 different size oxidation ponds and one site in waste receiver river. Samples were collected by triplicate in each sample sites and totally 12 sample sites were fixed. Some parameters like (pH, Temperature, Conductivity, and Turbidity) were measured in situ. ICP-OES used for analysis heavy metal. XLSTAT version 2014.5.03 was applied for analysis and interpreting the relationship of each water quality parameters using one way ANOVA and Pearson correlation. This study shows Conductivity, pH, were showed highly significance difference among oxidation ponds while temperature showed non-significance difference (a